Can stories reduce abortion stigma? Findings from a longitudinal cohort study. Issue 3 (4th March 2018) - Cockrill, Kate; Biggs, Antonia
Abstract: Women often hide or selectively disclose abortion experiences due to stigma. Secrecy can help women avoid stigma but may also result in isolation and a lack of social support and contribute to broader social silence. This study assesses whether a book-club intervention can support abortion disclosure among book club participants and improve participants' affective responses towards women who have abortions and abortion providers. A total of 109 women from 13 all-female book clubs located in 9 US states read and discussed a non-fiction book that included stories about pregnancy and abortion, participated in a book club discussion and completed baseline, immediate post-intervention and endline surveys. In 10 out of the 13 book club discussions, at least one member disclosed having had a previous abortion. Overall, 15 of the 19 women who privately reported having a previous abortion self-disclosed one or more abortions during the book club discussion. Following the book club intervention, women reported having more positive feelings toward women who have abortions and abortion providers. Greater improvement and longer lasting effects were seen in groups where there was also an in-person disclosure of abortion experience. Findings suggest that exposure to the stories of women who have had abortions can reduce abortion stigma.